Gambaran Kandungan Fe Pada ASI Ibu Menyusui Pada Enam Bulan Pertama - Umi Marifah (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: The research aims to describe the content of Fe in the breast milk of nursing mothersMethods: This research is descriptive with a cross-sectional research design. This study aims to determine the Fe content in breast milk at Puskesmas Tanah Kali Kedinding. The average content of Fe breast milk is 10.39 mg/ml.Results: As many as 16 people (57%) of breastfeeding mothers have Fe breast milk content below 10.39 mg/ml. The content of Fe breast milk in breastfeeding mothers is still below 10.39 mg/ml and as much as 43% above average (>10.39%).Conclusion: The content of Fe in breast milk in nursing mothers is low (<10.39%), and there is a high (>10.39%)